Kontribusi Sektor Pertanian Subsektor Tanaman Pangan terhadap PDRB pada Kabupaten Banjar (Pendekatan PDRB Hijau) - Erika Anindya Tyas Utari; Siti Mutmainah Zulfaridatulyaqin (Ecoplan, 2020)
Abstract - This study aims to determine and analyze the value of depletion, degradation, green contribution, and the agricultural sector's real contribution to the food crop subsector in Banjar District. Data is processed by mathematical calculations using the green GRDP approach. This research is a quantitative descriptive study. The data used is secondary data in the time series between 2015-2018 and supported primary data through unstructured interviews. The results showed a relatively large depletion and degradation value, amounting to IDR 378 billion in 2015, increasing by IDR 460.6 billion in 2016, decreasing to IDR 403.1 billion in 2017, and reducing again to IDR 364.8 billion in 2018. This enormous value is the environmental value lost due to agricultural activities. The farm sector's real contribution to the food crop sub-sector in Banjar Regency after calculating the amount of depletion and degradation to GRDP increased by an average of 47.81% in 2015-2018. The agricultural sector's real contribution to the food crops sub-sector in Banjar District shows a large figure because it has been included in calculating natural capital assets' environmental elements. This high real contribution value can be a way to increase regional income with the implication of ecological preservation that is sustainable. Keywords: Green GRDP, Agricultural Sector, Food Crops Subsector, Depletion, Degradation.